Analysis of Cell Kinetics Using a Cell Division Marker: Mathematical Modeling of Experimental Data - Bernard, Samuel (Biophysical Society, 2003)
We consider an age-maturity structured model arising from a blood cell proliferation problem. This model is “hybrid”, i.e., continuous in time and age but the maturity variable is discrete. This is due to the fact that we include the cell division marker carboxyfluorescein diacetate succinimidyl ester. We use our mathematical analysis in conjunction with experimental data taken from the division analysis of primitive murine bone marrow cells to characterize the maturation/proliferation process. Cell cycle parameters such as proliferative rate β, cell cycle duration τ, apoptosis rate γ, and loss rate μ can be evaluated from CarboxyFluorescein diacetate Succinimidyl Ester + cell tracking experiments. Our results indicate that after three days in vitro, primitive murine bone marrow cells have parameters β = 2.2 day(−1), τ = 0.3 day, γ = 0.3 day(−1), and μ = 0.05 day(−1).